Comparative effectiveness of neoadjuvant chemoradiotherapy versus chemotherapy alone followed by surgery for patients with stage IIIA non-small cell lung cancer. Issue 3 (June 2015) - Sher, David J.; Fidler, Mary Jo; Liptay, Michael J.; Koshy, Matthew
Highlights We compared preop chemoRT vs. chemo for stage IIIA NSCLC in the NCDB. There was no difference in overall survival. Pathologic response was improved with induction chemoradiotherapy. There was no difference in adverse surgical outcomes. PORT was harmful in patients with favorable post-chemotherapy pathology.